A meta-analysis of group Cognitive Behavioral Therapy (CBT) interventions for adolescents with depression. (August 2018) - Keles, Serap; Idsoe, Thormod
Abstract: The aim of this meta-analysis was to systematically examine the short- and long-term effects of group Cognitive Behavioral Therapy (CBT) for adolescent depression and to examine the role of various moderators of the reported effect sizes. A comprehensive literature search of relevant randomized-controlled trials identified 23 studies containing 49 post-intervention and 56 follow-up comparisons. Standardized mean differences (SMD) were calculated both for post-intervention and follow-up. A three-level random effects approach was used to model the dependent effect sizes. Group CBT was more efficacious than control conditions both at post-intervention (SMD = −0.28, 95% CI [-0.36, −0.19]) and at follow-up (SMD = −0.21, 95% CI [-0.30, −0.11]). Having an inactive control group was associated with a larger post-intervention effect size, while having a longer follow-up duration was associated with a smaller follow-up effect size. Even though the effect sizes are low, research suggests that group CBT is a significant treatment for adolescent depression.